THE 8 JANUARY 2006 EARTHQUAKE (MW 6.7) OFFSHORE KYTHIRA ISLAND, SOUTHERN GREECE: SEISMOLOGICAL, STRONG-MOTION, AND MACROSEISMIC OBSERVATIONS OF AN INTERMEDIATE-DEPTH EVENT - Konstantinou K.I.; Kalogeras I.S.; Melis N.S.; Kourouzidis M.C.; Stavrakakis G.N. (My University, 2006)
On 8 January 2006 at 11:34 GMT (13:34 local time), a strong earthquake with a moment magnitude of 6.7 occurred in southern Greece, off the eastern coast of the island of Kythira. The epicentral coordinates as estimated by the European Mediterranean Seismological Centre (EMSC-CSEM, http://emsc-csem.org were 36.31°N, 23.24°E, and the focal depth was 60 km. The shock was felt in a spatially extended area that covered Greece, Italy, Turkey, Egypt, Cyprus, Israel, Syria, Jordan, and Lebanon. Despite the large magnitude of the earthquake, the reported damage was not extensive mainly due to the intermediate focal depth. No casualties were reported and the structural damage to buildings was limited to the islands of Kythira and Antikythira and to the city of Chania, western Crete. Furthermore, landslides and/or rockfalls were reported only at the village of Mitata (Kythira island), where the main square and the road were damaged due to a landslide. Intermediate-depth earthquakes in this region are related to the southern Aegean subduction zone, which is referred to as the Hellenic arc (figure 1). The deformation that takes place along this arc is caused by the motion and collision of the southern part of the Eurasian plate with the African plate at a rate of 40–60 mm/year. The basic picture of the regional kinematics has not changed much since the early work of McKenzie (1972, 1978) but has been studied in more detail recently using GPS data (LePichon et al. 1995; McClusky et al. 2000; Nyst and Thatcher 2004, among others). The continuation of the Hellenic arc is interrupted by active fault zones with a perpendicular orientation relative to the boundary of the two plates (Lyberis et al. 1982). One of these structures exists in the vicinity of Kythira island and during the 20th century produced five …